DESCRIPTION OF THE COMPATIBILITY OF MEDICATION PRESCRIBING WITH THE NATIONAL FORMULARIUM IN BPJS PATIENTS IN THE OUTPATIENT POLICY OF INTERNAL MEDICINE AT EMC TANGERANG HOSPITAL FOR THE PERIOD OF JANUARY – MARCH 2023 - Rahajeng, Sunny Koswara (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
The Hospital Formulary is a list of drugs agreed upon by medical staff compiled by the Pharmacy and Therapy Committee/Team determined by the Hospital Management. The Hospital Formulary is prepared referring to the National Formulary and must be available to all prescribers, drug dispensers and drug providers in hospitals. The aim of this research is to determine the appropriateness of drug prescribing according to the National Formulary for BPJS patients in the internal medicine clinic at EMC Hospital Tangerang City for the period January – March 2023. The type of research is nonexperimental research with a descriptive approach, data collection was carried out retrospectively. Based on the results of the research, the description of the suitability of drug prescribing with the National Formulary in BPJS outpatient poly internal medicine patients at EMC Hospital Tangerang City for the period January – March 2023 can be concluded based on the characteristics of the gender and age categories of BPJS outpatient poly internal medicine patients, gender is the most the highest, namely female gender, 88 patients (55%) and the highest age, namely early adulthood (26–35 years) as many as 50 patients (31%), based on conformity between prescription writing and the National Formulary in BPJS internal medicine patients The highest number was in February with 24 recipes (40%).